Analisis Energi Pada Unit 2 Pembangkit Listrik Tenaga Gas (PLTG) Teluk Lembu Kapasitas 21.6 MW - Nur Indah Rivai; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Electrical energy is energy that is needed by society and industry. To fulfill this need, many power plants were built in Indonesia. Gas Turbine Power Plant (PLTG) is one type of power plant that supplies electricity in Indonesia. The installed power capacity of PLTG in Indonesia is 3,591 MW or 9.6% of the total power plant. PLTG spending in Indonesia is the fastest among other types of power plants, which is equal to 10% per year. This energy analysis is carried out by taking samples of the Teluk Lembu PLTG with a capacity of 21.6 MW. The purpose of this study is to calculate the thermal efficiency of a generator. And from the results of the calculation analysis, it was found that the compressor worked 3.40 MW, the heat entering was 65.75 MW, the work of the 48.63 MW turbine, the net work of 15.92 MW and the efficiency thermal was 24.23% Keywords: Gas turbine power plant, energy, efficiency thermal